Involvement of stress-released corticotropin-releasing hormone in the basolateral amygdala in regulating memory consolidation - Roozendaal, Benno (The National Academy of Sciences, 2002)
It is well established that adrenal stress hormone-induced activation of the basolateral complex of the amygdala (BLA) influences memory consolidation. The present experiments investigated the involvement of corticotropin-releasing hormone (CRH) in the BLA in modulating memory consolidation. Bilateral infusions of the CRH receptor antagonist [9–41]-α-helical CRH (0.3, 1.0, or 3.0 μg in 0.2 μl) administered into the BLA of male Sprague–Dawley rats immediately after aversively motivated inhibitory avoidance training produced dose-dependent impairment of 48-h retention performance. Because the CRH receptor antagonist infusions did not impair retention when administered into the BLA 3 h after training, the retention impairment selectively was due to time-dependent influences on memory consolidation. Furthermore, because immediate posttraining infusions of [9–41]-α-helical CRH into the adjacent central nucleus of the amygdala (CEA) were ineffective, the effect selectively involved the BLA. Immunocytochemistry showed that the aversive training stimulus of a single, brief footshock increased CRH levels in the CEA. These findings indicate that activation of CRH receptors in the BLA, likely by training-induced release of endogenous peptide originating from the CEA, participates in mediating stress effects on memory consolidation.